Corneal optical density: Structural basis, measurements, influencing factors, and roles in refractive surgery - He, Ye; Ma, Bo-Sheng; Zeng, Jun-Hao; Ma, Dai-Jin (Frontiers in Bioengineering and Biotechnology, 2023)
The cornea is the main refractive medium of the human eye, and its clarity is critical to visual acuity. Corneal optical density (COD) is an important index to describe corneal transparency. Intact corneal epithelial and endothelial cells, regular arrangement of collagen fibers in the stroma, and normal substance metabolism are all integral for the cornea to maintain its transparency. In the last two decades, the Pentacam Scheimpflug imaging system has emerged as a breakthrough for the measurement of COD (also called corneal densitometry). It has been found that a wide variety of factors such as age, refractive status, and corneal diseases can affect COD. Different corneal refractive surgery methods also change COD in different corneal regions and layers and affect visual acuity following the surgery. Thus, COD has gradually become a significant indicator to evaluate corneal health, one on which the attention of clinicians has been increasingly focused.